A Novel Rapid Fungal Promoter Analysis System Using the Phosphopantetheinyl Transferase Gene, npgA, in Aspergillus nidulans. Issue 4 (2nd October 2018) - Song, Ha-Yeon; Choi, Dahye; Han, Dong-Min; Kim, Dae-Hyuk; Kim, Jung-Mi
Abstract: To develop a convenient promoter analysis system for fungi, a null-pigment mutant (NPG) of Aspergillus nidulans was used with the 4′-phosphopantetheinyl transferase (PPTase) gene, npgA, which restores the normal pigmentation in A. nidulans, as a new reporter gene. The functional organization of serially deleted promoter regions of the A. nidulans trpC gene and the Cryphonectria parasitica crp gene in filamentous fungi was representatively investigated to establish a novel fungal promoter assay system that depends on color complementation of the NPG mutant with the PPTase npgA gene. Several promoter regions of the trpC and crp genes were fused to the npgA gene containing the 1, 034-bp open reading frame and the 966-bp 3' downstream region from the TAA, and the constructed fusions were introduced into the NPG mutant in A. nidulans to evaluate color recovery due to the transcriptional activity of the sequence elements. Serial deletion of the trpC and crp promoter regions in this PPTase reporter assay system reaffirmed results in previous reports by using the fungal transformation step without a laborious verification process. This approach suggests a more rapid and convenient system than conventional analyses for fungal gene expression studies.